Penggunaan Air Kelapa Muda Sebagai Zat Pengatur Tumbuh Terhadap Daya Kecambah, Vigoritas, Berat Kering Biji Tanaman Kelor (Moringa oleifera) - Dodi Devitriano; Hutwan Syarifuddin (Universitas Batanghari Jambi, 2021)
The more common methode for planting moringa plant is using seed, because this plant produces a lot of seeds. However, the resulting seeds have a hard enaugh seed coat so that. These conditions can affect and even thwart germination, vigor and growth of the plant. This Study aims to determine the proper dosage of young coconut water to be used in growing moringa seeds, so that later it become a recommendation for formers in the development of moringa plants. This research was conducted using a green house and laboratory scale method with the media that had been prepared for germination obsevations were carried out for two weeks to obtain data according to the observed parameters which included capacity, Vigority and dryweight of moringa plants. The result of the analysis of variety showed that the concentration of young coconut water had no significant effect (P>0.05) on the germination, vigor and dryweight of moringa plants. Likewise, the interaction between immersion time and coconut water concentration had no significant effect (P>0.05) on the observed variables. This situation is due to the fact that not all moringa seeds undergo the imbibition process properly so that they effect the observed variables.